Development of e-commerce applications to increase sales turnover of agricultural products for Ibnu Al Mubarok Islamic Boarding School Pekanbaru - Guntoro Guntoro; Lisnawita Lisnawita; Anto Ariyanto (Community Empowerment, 2022)
E-commerce is an internet-based technology that can be used to market products widely. Ibnu Al-Mubarok Islamic Boarding School is one of the agro-tourism boarding schools that has many products in the fields of agriculture, animal husbandry, and SMEs. However, in order to support economic independence, the range of product marketing is still limited. This service activity resulted in the Al-Mubarok Farm E-Commerce application. With this application, Al-Mubarok Islamic Boarding School Pekanbaru is able to increase promotion and sales turnover of agricultural products.